A Study on Public Perceptions of Carbon Neutrality in China: has the Idea of ESG Been Encompassed? - Li, Rita Yi Man; Wang, Qianqian; Zeng, Liyun; Chen, Hong (Frontiers in Environmental Science, 2023)
China is currently the second-largest economy in nominal gross domestic product and one of the largest carbon emitters. It has committed to achieving carbon neutrality by 2060 and used various means to reduce carbon emissions during industrial transformation and rapid economic development. As people’s support to achieve the goal of carbon neutrality affects the outcome of the national carbon neutrality goal, this study reviewed the public’s perception of carbon neutrality. It collected 7,038 posts from Weibo, China’s most popular social platform. It revealed people’s concerns about carbon neutrality are mainly related to the environment (e.g. low carbon, sustainable and wind power), social (e.g. country and poverty) and governance (responsibility, government report). Weibo users believe that achieving carbon-neutrality allows us to pursue a better life. Among the data collected, positive emotion blogs (83.9%) were approximately eight times more than negative blogs (9.9%) and only 6.3 % were neutral. The reasons may be because carbon neutrality achievements are positive in general and supported by the people in China.